Multilayered nano Ti3C2Tx electrode: An ultrasensitive electrochemical sensor for rutin antioxidant detection - Jagadeesh Ramadoss,; Sonachalam, Arumugam (Malaysian NANO-An International Journal, 2023)
Multilayer two-dimensional (2D) structures (MXenes) provide promising advantages in biomedical applications. Using SEM and XRD characterization techniques, the synthesized substance was identified. Our results show that Ti3C2Tx-GCE possesses a significant number of active sites, enhancing its electrocatalytic activity and electrochemical sensing abilities for RT oxidation. The multilayered Ti3C2Tx-GCE that was produced had good electrochemical properties and acceptable pore structures. Additionally, it exhibited remarkable linearity starting from 1 to 10 μM and demonstrated high sensitivity for the electrochemical measurement of RT, with an impressively low limit of detection (LOD) of 0.345 μM. EIS studies revealed that the synthesized multilayered Ti3C2Tx possessed a significantly low charge transfer resistance and a high electron transfer rate constant. Our research lays the groundwork for designing a multilayered Ti3C2Tx network, which opens up intriguing possibilities for creating high-performance electrochemical sensors for use in biomedicine and clinical settings.